Impact of herbicides Imazethpayr (Pursuit) and Oxyfluorfen (Goal) on weed control and yield of groundnut (Arachis hypogaea L.) - ELsiddig AbdAlla, Mawahib Ahmed; ELamin, Salah ELTom; Khair, Saif ELdin Mohamed; Haroun, Nayla E.; Mohamed, Ekhlas Hussein (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
Trials were initiated in 2007 to evaluate systems of weed management in peanut using herbicides. Two trials were conducted at Sudan University of Science and Technology, College of Agricultural Studies and Research Farm of University of Khartoum, Faculty of Agriculture, Shambat, to evaluate the efficacy of imazethapyr and oxyfluorfen herbicides for weed control at different rates, tolerance, and yield of the crop.The imazethapyr was used at rates of 0.175, 0.25, and 0.5 L/fed, for and oxyfluorfen at rates of 0.25, 0.5 and 1.0 L/fed. Moreover, the two products were also combined at low, medium and high rates. The results showed significant differences at medium and high rates of the two herbicides combination and at hand weeding as compared to the unweeded control in the variety Medani and Sodari for growth and yield components. The highest reduction in yield was found in unweeded control, it was 49.89% in season 2007/2008 and 45.31% in season 2008/2009. Significant differences were also observed in number of pods per plant, 100 pod weights, in comparison with the unweeded control